KOMPATIBILITAS CENDAWAN METARHIZIUM ANISOPLIAE (METSCHN.) SOROKIN DENGAN NEMATODA ENTOMOPATOGEN STEINERNEMA SP. - Rosyidi, Imron; Purnomo, Hari; Haryadi, Nanang Tri; Hoesain, Mohammad (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2017)
Compatibility Metarhizium anisopliae (Metschn.) Sorokin with entomopathogenic nematode Steinernema sp. Metarhizium anisopliae (Metschn.) Sorokin and entomopathogenic nematode Steinernema sp. can be used as biological control of insect pests. The objective of this research was to identify compatibility between fungus M. anisopliae with entomopathogenic nematode Steinernema sp. This research was conducted using a completely randomized design (CRD) consisting of 5 treatments and repeated 5 times. The treatment used was M. anisopliae isolates Jombang 1 with Steinernema sp. (M1), M. anisopliae Jombang 2 with Steinernema sp. (M2), M. anisopliae isolates Kediri with Steinernema sp. (M3), M. anisopliae isolates Bondowoso with Steinernema sp. (M4), and M. anisopliae isolates Banyuwangi with Steinernema sp. (M5). Based on this research result, compatibility between the fungus M. anisopliae with entomopathogenic nematode Steinernema sp. was antagonistic. This occurs due to the symbiotic bacteria Xenorhabdus sp. that produced compounds antimycotic and capable to inhibit the growth of fungus M. anisopliae.